2021
DOI: 10.1155/2021/6670007
|View full text |Cite
|
Sign up to set email alerts
|

D‐Limonene Alleviates Acute Kidney Injury Following Gentamicin Administration in Rats: Role of NF‐κB Pathway, Mitochondrial Apoptosis, Oxidative Stress, and PCNA

Abstract: Clinical application of gentamicin (GM) is well known to be associated with the development of acute kidney injury (AKI). This study was the first to investigate the possible protective effects of D-limonene (D-lim) on AKI following GM administration in rats. 32 rats arranged in four groups ( n = 8 ): (1) the control group received saline intraperitoneally (0.5 ml/day) and orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 77 publications
4
11
0
Order By: Relevance
“…Hence, we suggested that HUCB-MNCs could restore the normal expression of Kim-1 level by minimizing the observed renal damage. It has been proposed that inflammation plays a role in the pathogenesis of GM-induced nephrotoxicity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we suggested that HUCB-MNCs could restore the normal expression of Kim-1 level by minimizing the observed renal damage. It has been proposed that inflammation plays a role in the pathogenesis of GM-induced nephrotoxicity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some animal models have been used to investigate possible pathways for HUCB MNCs' protective properties ( 26 , 35 , 43 , 58 60 ). Most SCs were gradually transferred to injured sites or the liver, spleen, kidney, and bone marrow ( 61 , 62 ) to recruit SCs to repair the damage caused by release factors ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, hesperidin significantly increases the level of α-Klotho (α-KL) in serum, liver, and kidney tissues and significantly reduces the levels of blood urea nitrogen (BUN) and creatinine in fibroblast growth factor-23 (FGF-23) in kidney tissues and serum [49]. On the other hand, D-limonene of essential oil orange peels may increase GFR following the amelioration of renal histopathological alterations and finally lowering serum levels of urea and creatinine [50]. Effect of native lycopene, hesperidin, essential oil and their nano-formulation forms on liver function.…”
Section: Effect Of Native Lycopene Hesperidin and Essential Oil And Their Nano-formulation Form On Renal Functionmentioning
confidence: 99%
“…While, hesperidin significantly increases the level of α-Klotho in serum, liver, and kidney tissues of diabetic rats, and consequently significantly reduce the levels of AST and ALT, so it helps in maintaining normal function by accelerating the regenerative capacity of liver cells [54]. The antioxidative protective effects of essential oil might be associated with its abilities to scavenge ROS and/or induce the gene expression of antioxidant enzymes [50].…”
Section: Effect Of Native Lycopene Hesperidin and Essential Oil And Their Nano-formulation Form On Renal Functionmentioning
confidence: 99%